Atypical Distribution of Inflammation in Newly Diagnosed Ulcerative Colitis is not Rare - Sang Hyoung Park; Suk-Kyun Yang; Soo-Kyung Park; Jong Wook Kim; Dong-Hoon Yang; Kee Wook Jung; Kyung-Jo Kim; Byong Duk Ye; Jeong-Sik Byeon; Seung-Jae Myung; Jin-Ho Kim (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Appendiceal orifice inflammation (AOI) is a common ‘skip lesion’ in patients with ulcerative colitis (UC). However, other skip lesions are less well known.